2012
DOI: 10.1111/j.1600-0765.2012.01473.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of root surface microtopography following the use of four instrumentation systems by confocal microscopy and scanning electron microscopy: an in vitro study

Abstract: Three of the four instruments tested for root planing reduced surface roughness; however, the piezosurgery ultrasonic scaler produced the smoothest surface. The termination diamond burs (40 μm) produced a rougher surface than the ultrasonic instruments and the hand curettes. Further clinical studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
5
16
0
Order By: Relevance
“…Clinical and experimental trials offer the highest level of scientific evidence, and the present results are similar to findings published by the few in‐vivo studies carried out in patients . Santos et al .…”
Section: Discussionsupporting
confidence: 90%
“…Clinical and experimental trials offer the highest level of scientific evidence, and the present results are similar to findings published by the few in‐vivo studies carried out in patients . Santos et al .…”
Section: Discussionsupporting
confidence: 90%
“…compared the root surface roughness after using Gracey curettes, termination diamond burs (40 μm), a piezoceramic ultrasonic scaler, and a piezosurgery ultrasonic scaler, using confocal microscopy and scanning electron microscopy. [24] They found that the termination diamond burs (40 μm) produced a rougher surface than the ultrasonic instruments and the hand curettes. Whereas Dahiya et al .…”
Section: Discussionmentioning
confidence: 99%
“…The Ra value of the enamel surface has been reported to be in the range of 37.0–127.9 nm [1112]. The Ra value of the root surface has been reported to be in the range of 0.41–1.12 µm [4]. Various methods of root planing have been reported to produce a root surface roughness in the range of 0.35–4.90 µm depending on the instruments used [451314].…”
Section: Methodsmentioning
confidence: 99%
“…The Ra value of the root surface has been reported to be in the range of 0.41–1.12 µm [4]. Various methods of root planing have been reported to produce a root surface roughness in the range of 0.35–4.90 µm depending on the instruments used [451314]. The plates with an Ra value corresponding to a high-nanometer dimension (867.0±168.6 nm) and a mid-nanometer dimension (505.3±115.3 nm) were rougher than the enamel surface and within the range of the Ra reported on the untreated root surface or the root surface after root planing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation